Assessment of the advancement of technology in the small scale poultry in San Jose, Batangas - Perculeza, Roberto V., Jr
--The study will tackle in the technologies such as automatic grain feeder and elevated water tank with inter-connected piping, drinking cups and nipples. No available study has been conducted to identify the factors affecting the exploitations of these poultry technologies in small scale poultry farming. Therefore, it will identify the issues concerning the use of advanced technologies on a poultry farm including its feasibility whether to adopt or not. It will also answer the question "is it feasible for the small scale enterprise to adopt the current technology in an SME poultry farm?"--